Citizenship Education as a Vehicle for Nation Building: Perspective of Nigeria Citizens - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study investigated the role of citizenship education as a vehicle for nation building: perspective of Nigeria citizens. The study was guided by four objectives and also answered four research questions. The study used social constructivist theory propounded by Lev Vygotsky in the mid 20th century. The study employed a cross-sectional survey research design targeting Nigerian citizens, including students, civil servants, public servants, policymakers, business people, parents, politicians, and traditional rulers. A sample of 400 respondents was selected through stratified sampling to enhance representativeness, precision, and reliability, particularly for studies on citizenship education and nation-building. Data was collected using a structured questionnaire developed by the researcher, comprising demographic questions (Section A) and 30 items under four subheadings on a four-point Likert scale (Section B). Content validity was ensured through expert review, and reliability was confirmed via split-half method, yielding a reliability coefficient of 0.87. Data collection was conducted online via Google Forms, and analysis was performed using descriptive statistics through mean and standard deviation computed in SPSS version 25.0. The analysis revealed that citizens have various and varying perception towards nation building and the study also identify corruption, tribalism, political instability, ethnic sentiments, and religious conflict as significant challenges to nation-building in Nigeria among others. The study recommended among other things that, Nigerian government and educational institutions intensify efforts to integrate comprehensive citizenship education into all levels of the educational curriculum. And the curriculum should emphasize national unity, democratic values, and the importance of inclusiveness in governance.